(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Preeclampsia is a major cause of maternal morbidity and mortality with unknown aetiology. Placental hypoperfusion and diffuse endothelial cell injury are considered the central pathological process. Many adipocyte hormones like leptin play an important role in the inflammatory and atherosclerotic process and may be used as a marker for preeclampsia. Objective:To find the role of serum leptin measurement in pregnant women as a marker of preeclampsia. Methods: Seventy six primigravida women in their 3rd trimester of pregnancy were studied; 44 of them with severe preeclampsia, while the other 32 women with normal blood pressure without any history of previous diseases. Blood samples were taken for serum leptin, uric acid and creatinine levels, urine samples were collected for albumin. Serum leptin level was measured by ELISA kits. Result:Serum leptin and uric acid levels but not the creatinine was different in eclamptic group than control group. Mean age, height and weight were not different between the two groups. The systolic and diastolic blood pressures were also different between the two groups. 26 cases (59.1%) had proteinuria of 3+ albumin and 18 cases (40.9%) with 4+. Conclusion:Elevated serum leptin level can be used as a marker in the assessment of preeclampsia. Key words: Primigravida, preeclampsia, serum lipten.